FIKIH ZAKAT: KONSEP, JENIS, PENGELOLAAN, DAN RELEVANSINYA DI ERA MODERN - Uswatun Hasanah; Ummu Diana Munawwarah (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2025)
Abstrak Zakat merupakan salah satu instrumen penting dalam Islam yang memiliki fungsi ibadah dan sosial ekonomi. Kajian fikih zakat mencakup pemahaman konseptual, jenis-jenis zakat, pengelolaan, hingga aplikasinya dalam konteks kekinian. Secara etimologis, zakat bermakna penyucian dan pertumbuhan, sedangkan secara terminologis merujuk pada kewajiban mengeluarkan sebagian harta kepada golongan tertentu yang telah ditetapkan oleh syariat. Jenis-jenis zakat antara lain zakat fitrah, zakat mal (yang meliputi hewan ternak, barang tambang, hasil pertanian, perdagangan, dan profesi). Kedelapan golongan penerima zakat (mustahiq) ditegaskan dalam Al-Qur'an, termasuk fakir, miskin, amil, muallaf, budak, gharim, fisabilillah, dan ibnu sabil. Historisnya, pengelolaan zakat sejak masa Rasulullah hingga masa tabi’in mengalami dinamika. Masa Umar bin Abdul Aziz dianggap sebagai era emas dalam pengelolaan zakat secara terstruktur dan profesional. Di era modern, zakat dikelola secara sistematis melalui lembaga-lembaga resmi dengan prinsip transparansi, profesionalisme, dan akuntabilitas. Pemerintah juga berperan aktif dalam pembinaan dan pengawasan. Zakat tak hanya didistribusikan secara konsumtif, tetapi juga produktif dalam bentuk pemberdayaan ekonomi umat. Dengan manajemen zakat yang baik meliputi perencanaan, pengorganisasian, pengarahan, dan pengawasan zakat diharapkan mampu menjadi solusi nyata dalam mengatasi kemiskinan dan ketimpangan sosial. Kata kunci: Zakat, Mustahiq, Muzakki, Era Modern, Ekonomi Islam.   Abstract Zakat is an important instrument in Islam that has both worship and socio-economic functions. The study of zakat jurisprudence encompasses conceptual understanding, types of zakat, management, and its application in the current context. Etymologically, zakat means purification and growth, while terminologically it refers to the obligation to distribute a portion of one's wealth to certain groups as determined by sharia. Types of zakat include zakat fitrah (fitrah), zakat mal (which includes livestock, minerals, agricultural products, trade, and professions). The eight categories of zakat recipients (mustahiq) are emphasized in the Qur'an, including the poor, needy, amil (manager of wealth), converts to Islam, slaves, gharim (gharim), fisabilillah (the beneficiaries of Allah), and ibn sabil (the beneficiaries of Allah). Historically, zakat management has undergone dynamics from the time of the Prophet Muhammad (peace be upon him) to the time of his successors. The era of Umar ibn Abdul Aziz is considered the golden era for structured and professional zakat management. In the modern era, zakat is managed systematically through official institutions based on the principles of transparency, professionalism, and accountability. The government also plays an active role in guidance and supervision. Zakat is distributed not only for consumption but also productively through economic empowerment of the community. With proper zakat management, encompassing planning, organization, direction, and supervision, zakat is expected to become a real solution to addressing poverty and social inequality. Keywords: Zakat, Mustahiq, Muzakki, Modern Era, Islamic Economics.